A composite mold, a manufacturing method, and a casting process for titanium and zirconium alloy castings

CN122955869APending Publication Date: 2026-10-23XIAN PUMP & VALVE GENERAL FACTORY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611354237.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]针对上述现有技术存在的问题,本发明的目的在于提供一种复合模具、制备方法及钛、锆合金铸件的铸造工艺,该模具包括可反复使用的石墨外形模和一次性熔模精铸型壳型芯,降低制作成本和简化制作工艺,使得铸造工艺可反复使用石墨外形模,搭配一次性低成本熔模精铸型壳型芯,在钛、锆合金铸件铸造过程中,石墨外形模耐高温、化学稳定、高强度不与钛、锆熔体反应,熔模精铸型壳型芯高精度、可复杂成型,且成本低廉,在制备钛、锆合金铸件时,有效抑制界面反应,减少铸件缺陷,显著降低生产成本,提高生产效率,适用于复杂内腔钛、锆合金铸件的规模化生产

Benefits of technology

[0014]本发明的有益效果是:本发明公开了一种复合模具、制备方法及钛、锆合金铸件的铸造工艺,与现有技术相比,本发明的改进之处在于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955869A_ABST
    Figure CN122955869A_ABST
Patent Text Reader

Abstract

The present application relates to titanium, zirconium alloy precision casting technical field, in order to solve the existing titanium, zirconium alloy casting mold in the actual use process exists the problem of poor precision even failure and high cost, the present application provides a kind of composite mould, preparation method and the casting process of titanium, zirconium alloy casting, the mould includes reusable graphite shape mould and disposable investment casting shell core, reduce production cost and simplify production process, so that the casting process reusable graphite shape mould, with disposable low-cost investment casting shell core, in the titanium, zirconium alloy casting process, graphite shape mould is resistant to high temperature, chemical stability, high strength does not react with titanium, zirconium melt, investment casting shell core high precision, complex forming, and low cost, when preparing titanium, zirconium alloy casting, effectively inhibit interface reaction, reduce casting defects, significantly reduce production cost, improve production efficiency, suitable for complex inner cavity titanium, zirconium alloy casting mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of precision casting technology for titanium and zirconium alloys, and in particular to a composite mold, its preparation method, and the casting process for titanium and zirconium alloy castings. Background Technology

[0002] Titanium and zirconium alloys possess high specific strength, excellent corrosion resistance, and superior high-temperature performance, making them widely used in aerospace, chemical equipment, and high-end machinery manufacturing. However, titanium and zirconium metals are extremely chemically reactive. In their molten state at high temperatures, titanium and zirconium alloys readily undergo violent interfacial reactions with conventional mold materials, leading to defects such as oxidation, sand adhesion, inclusions, porosity, and cracks on the casting surface, severely impacting the casting quality and mechanical properties.

[0003] Existing titanium and zirconium alloy casting molds generally use integral graphite molds. Graphite is heat-resistant, chemically stable, and does not react with the molten titanium and zirconium alloys. However, the core, due to its complex structure and being made of graphite, is usually made in multiple parts, which are then fixedly connected to form the core. If the core is not securely fixed, it will collapse within the mold cavity, rendering the titanium and zirconium alloy casting unusable. Even if it doesn't collapse, the precision error of the resulting titanium and zirconium alloy casting will increase. Furthermore, integral graphite molds need to be broken during demolding and cannot be reused. The price of graphite materials has been rising continuously in recent years, resulting in high mold manufacturing costs, making it difficult to meet the demands of large-scale, low-cost production. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention aims to provide a composite mold, a preparation method, and a casting process for titanium and zirconium alloy castings. The mold includes a reusable graphite outer mold and a disposable investment casting shell / core, reducing manufacturing costs and simplifying the manufacturing process. This allows for the repeated use of the graphite outer mold in the casting process, combined with the disposable, low-cost investment casting shell / core. During the casting of titanium and zirconium alloy castings, the graphite outer mold exhibits high temperature resistance, chemical stability, and high strength, without reacting with the titanium and zirconium melt. The investment casting shell / core offers high precision, can handle complex molding processes, and is inexpensive. In the preparation of titanium and zirconium alloy castings, this effectively suppresses interfacial reactions, reduces casting defects, significantly lowers production costs, and improves production efficiency. It is suitable for the large-scale production of titanium and zirconium alloy castings with complex internal cavities.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] The first objective of this invention is to provide a method for preparing a composite mold, the method comprising: Graphite outer mold one and graphite outer mold two are prepared using graphite electrode material. Graphite outer mold one and graphite outer mold two have the same structure and are connected and snapped together to form a hollow graphite outer mold. A hollow core matrix was prepared using PLA plastic and 3D printing technology. Apply a medium-temperature wax liquid with a temperature range of 70-90℃ to the inner cavity of the core substrate to form a medium-temperature wax layer. Then, clean the medium-temperature wax layer with wax remover and distilled water in sequence. Dry it at a temperature of 22℃-26℃ for 24 hours to obtain core substrate A. Two layers of surface slurry were applied to the inner cavity of core substrate A, and surface sand was sprinkled after each layer was applied. The core substrate B was obtained by drying at 20℃-22℃ for 24 hours. Apply a layer of transition layer slurry to the inner cavity of core substrate B, sprinkle transition layer sand on it, and dry it at 20℃-22℃ for 24 hours to obtain core substrate C; Five to ten layers of backing slurry are applied to the inner cavity of the core substrate C. Backing sand is sprinkled on each layer. The core substrate D is obtained by drying at 24℃-26℃ for 12 hours. At a temperature of 1050℃-1150℃, the core matrix D is calcined for 2-4 hours, and the core matrix A is burned off to obtain the investment casting shell core. The investment casting shell core is installed in the graphite outer mold one, and then the graphite outer mold two is connected and fixed to the graphite outer mold one to form a composite mold.

[0007] Preferably, the graphite electrode has a bulk density of 1.75 g / cm³-1.80 g / cm³ and a room temperature flexural strength of 40 MPa-45 MPa.

[0008] Preferably, the upper ends of the inner cavities of the first graphite mold and the second graphite mold are provided with positioning steps at the same position, and the upper end of the core substrate is provided with a positioning groove that fits the positioning steps.

[0009] Preferably, five to ten layers of backing slurry are applied to the inner cavity of the core substrate C. During the process of applying each layer of backing slurry, after the third layer of backing sand is applied, wire mesh is attached to the inner cavity of the core substrate C, and wire is wrapped and bound to the outer wall of the core substrate C.

[0010] Preferably, the core substrate D is baked at a temperature of 1050℃-1150℃ for 2h-4h. After the core substrate A is burned off, all the iron wires on the outer wall of the core substrate D are cut off.

[0011] The second objective of this invention is to provide a composite mold, which is prepared based on a composite mold preparation method.

[0012] A third objective of this invention is to provide a casting process for titanium and zirconium alloy castings, wherein the casting process is based on a composite mold and includes: The composite mold is preheated to 300℃-400℃ using a tabletop resistance furnace and held at that temperature for 1-2 hours to obtain a preliminary composite mold. In a vacuum environment, within a time period of 6s-15s, titanium and zirconium alloy melt is poured into the pores between the investment casting shell core and the graphite outer mold in the preliminary composite mold. After cooling to room temperature, the graphite outer mold is removed, and the investment casting shell and core are removed by means of instruments or water blasting to obtain titanium and zirconium alloy castings.

[0013] Preferably, the temperature of the titanium-zirconium alloy melt is 80°C-120°C higher than the alloy liquidus temperature.

[0014] The beneficial effects of this invention are: This invention discloses a composite mold, a preparation method, and a casting process for titanium and zirconium alloy castings. Compared with the prior art, the improvement of this invention lies in: (1) The composite mold of the present invention includes a graphite outer mold and an investment casting shell core nested together. The graphite outer mold consists of a graphite outer mold one and a graphite outer mold two that can be interlocked. The graphite outer mold one and the graphite outer mold two can be reused repeatedly during the casting process of titanium and zirconium alloy castings and are easy to assemble with the investment casting shell core. The graphite outer mold is resistant to high temperature, chemically stable and has high strength, effectively avoiding reaction with the titanium and zirconium alloy melt, and is fully compatible with the production of titanium and zirconium alloy castings.

[0015] Investment casting shells and cores use low-cost materials, can prepare arbitrarily complex internal cavities, and have high dimensional accuracy, low cost, and are easy to disassemble. Under the premise that the core needs to be broken for each titanium or zirconium alloy casting, the low-cost investment casting shells and cores can greatly reduce the problem of high cost and one mold per mold of traditional graphite cores, thus significantly reducing the mold cost for preparing titanium and zirconium alloy castings.

[0016] (2) The graphite outer mold and the investment casting shell core composed of multi-layer slurry, transition slurry, back slurry, and back sand in this invention can significantly reduce the reaction between the titanium and zirconium alloy melt and the mold when preparing titanium and zirconium alloy castings, reduce defects such as oxidation, porosity, cracks, and sand adhesion, and improve the mechanical properties and yield of the castings. Moreover, the positioning steps set in the graphite outer mold are engaged and positioned with the mating groove of the investment casting shell core, and the fitting clearance is controllable, the positioning is firm, and it effectively prevents sparking and misalignment.

[0017] The core substrate for making the investment casting shell core is made using 3D printing technology. It only requires coating multiple layers of slurry, transition layer slurry, back layer slurry, and back layer sand in its inner cavity. It does not require an overall investment casting shell, saving refractory materials, reducing production costs, and making it suitable for large-scale production. Attached Figure Description

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. In the accompanying drawings: Figure 1 This is a schematic diagram of the core substrate provided in an embodiment of the present invention; Figure 2 This is a schematic diagram of the positioning steps on the graphite outer mold one or graphite outer mold two provided in the embodiments of the present invention; The attached figures are labeled as follows: 1. Positioning step; 2. Positioning groove. Detailed Implementation

[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0020] Example 1: like Figures 1 to 2 As shown, this embodiment of the invention provides a method for preparing a composite mold, specifically including the following steps: S1. Graphite mold one and graphite mold two are prepared using high-purity, dense graphite electrode material. Graphite mold one and graphite mold two are connected and interlocked to form a hollow graphite mold.

[0021] In this embodiment, high-purity dense graphite electrode material with a bulk density of 1.80 g / cm³ and a room-temperature flexural strength of 45 MPa is selected. It is processed by a CNC machining center into two identical graphite outer molds, Graphite Outer Mold 1 and Graphite Outer Mold 2. Both are hollow structures, and they are snapped together to form a hollow graphite outer mold. The two molds are joined from left to right. Positioning steps 1 are machined at the same position on the upper end of the inner wall of both the graphite outer molds. The dimensions of the positioning steps 1 are adapted to the end of the core, allowing the end of the core substrate to engage with the positioning steps 1 during installation. After the end of the core substrate engages with the positioning steps 1, the gap between them is controlled within 0.2 mm.

[0022] S2. A hollow core matrix is ​​prepared using PLA plastic and 3D printing technology.

[0023] In this embodiment, the prepared core substrate is a hollow structure with a thickness of 8mm. The shape of the core substrate is consistent with the complex internal cavity structure of the casting. A positioning groove 2 is provided on the upper outer wall of the core substrate. The overall size of the positioning groove 2 is smaller than the size of the positioning step 1, preferably less than 0.2mm.

[0024] S3. Apply a medium-temperature wax liquid with a temperature range of 70-90℃ to the inner cavity of the core substrate to form a medium-temperature wax layer. Then, clean the medium-temperature wax layer with wax remover and distilled water in sequence. Dry at 22℃ for 24 hours to obtain core substrate A.

[0025] In this embodiment, a medium-temperature wax liquid with a temperature range of 70°C is used to coat the inner cavity of the core substrate, thereby forming a medium-temperature wax layer in the inner cavity of the core substrate. Then, the medium-temperature wax layer is cleaned with a wax remover, and finally the residue is cleaned again with distilled water. The core substrate A is obtained by drying at 22°C for 24 hours.

[0026] S4. Apply two layers of surface slurry to the inner cavity of core substrate A, sprinkle surface sand after each layer, and dry at 20℃ for 24 hours to obtain core substrate B.

[0027] In this embodiment, two layers of surface slurry are applied to the inner cavity of the core substrate A. Surface sand is sprinkled on each layer of surface slurry, resulting in a total surface coating thickness of 0.8 mm. The coating is dried at 20°C for 24 hours. Finally, the sand particles at the edge of the opening of the core substrate A are scraped off to obtain the core substrate B. The surface slurry is composed of a mixture of surface-specific adhesive and yttrium oxide powder, with a yttrium oxide powder:surface-specific adhesive ratio of 3.8-4.5:1. The surface sand is at least one of yttrium oxide or white corundum.

[0028] S5. Apply a layer of transition layer slurry to the inner cavity of core substrate B, sprinkle transition layer sand, and dry at 20℃ for 24 hours to obtain core substrate C.

[0029] In this embodiment, a transition layer slurry is applied to the inner cavity of the core substrate B, and transition layer sand (40-mesh mullite sand) is immediately sprinkled on top. The mixture is then dried at 20°C for 24 hours. The sand particles at the edges of the opening of the core substrate B are cleaned to obtain the core substrate C. The transition layer slurry consists of silica sol, wetting agent, bauxite powder, and mullite powder; the transition layer sand is fine mullite sand.

[0030] S6. Apply ten layers of backing slurry to the inner cavity of the core substrate C, and sprinkle backing sand after each layer. Dry at 24°C for 12 hours to obtain the core substrate D. After applying the third layer of backing sand, attach wire mesh to the inner cavity of the core substrate C for reinforcement, and wrap and bind the outer wall of the core substrate C with wire.

[0031] In this embodiment, 10 layers of backing slurry are applied to the inner cavity of the core substrate C. After each layer of backing slurry is applied, backing sand (20-mesh mullite sand) is sprinkled on top. The mixture is dried at 24°C for 12 hours, and excess sand is removed from the edges of the opening of the core substrate C. After the third layer of backing sand is applied, a wire mesh of appropriate size is used to reinforce the inner cavity wall of the core substrate C. The outside of the substrate is wrapped and bound with φ1mm wire. After binding, backing slurry and backing sand are applied again. The backing slurry has the same composition as the transition layer slurry, and the backing sand is coarse mullite sand.

[0032] S7. At a temperature of 1150℃, the core substrate D is baked for 4 hours to burn off the core substrate A, and all the iron wires on the outer wall of the core substrate D are cut off to obtain the investment casting shell core.

[0033] In this embodiment, the core substrate D is baked at 1150°C for 4 hours to burn off the core substrate A. Then, all the iron wires outside the core substrate D are cut off to obtain a casting shell core with a room temperature flexural strength of 11 MPa, which is composed of multi-layer slurry, transition slurry, back slurry, and back sand. A docking groove corresponding to the positioning groove 2 is formed on the outside of the casting shell core.

[0034] S8. Install the investment casting shell core into the inner cavity of the graphite outer mold one, and make the mating groove engage with the positioning step 1 of the graphite outer mold one. Then, assemble and fix the graphite outer mold two with the graphite outer mold one to form a composite mold.

[0035] In this embodiment, the investment casting shell core is installed in the inner cavity of graphite outer mold one or graphite outer mold two, and the mating groove is engaged with the positioning step 1 of graphite outer mold one or graphite outer mold two. Then, the corresponding graphite outer mold one or graphite outer mold two are mated and positioned and connected by positioning pins to obtain a composite mold.

[0036] A casting process for titanium-zirconium alloy castings, the specific steps of which are as follows: S1. Preheat the composite mold to 400℃ using a benchtop resistance furnace and hold for 2 hours to obtain a preliminary composite mold. This process is used to reduce the temperature difference between the composite mold and the molten metal, improve the fluidity of the molten metal, and facilitate filling.

[0037] S2. Under vacuum conditions, within a 15-second time period, titanium and zirconium alloy melt is steadily poured into the pores between the investment casting shell core and the graphite outer mold in the preliminary composite mold, and the temperature of the titanium and zirconium alloy melt is 100°C higher than the alloy liquidus temperature.

[0038] S3. After the titanium and zirconium alloy melt cools to room temperature, first remove the graphite outer mold, and then remove the investment casting shell and core by means of instruments or water blasting to obtain the titanium and zirconium alloy casting.

[0039] These titanium and zirconium alloy castings can replace stainless steel castings in chemical equipment, solving problems such as acid and alkali corrosion; they can replace aerospace equipment to reduce weight and withstand alternating loads; and they can provide long-term corrosion resistance in marine energy equipment.

[0040] Example 2: This embodiment provides a method for preparing a composite mold and a casting process for titanium and zirconium alloy castings. Specifically, the composite mold is a composite mold for a small gate valve body, and the casting process for the titanium and zirconium alloy castings is the casting process for the small gate valve body.

[0041] The preparation process of the composite mold for the valve body of the small shut-off valve is as follows: S1. Graphite mold one and graphite mold two are prepared using high-purity, dense graphite electrode material. Graphite mold one and graphite mold two are connected and interlocked to form a hollow graphite mold.

[0042] In this embodiment, high-purity dense graphite electrode material with a bulk density of 1.75 g / cm³ and a room-temperature flexural strength of 40 MPa is selected. It is processed by a CNC machining center into two identical graphite outer molds, Graphite Outer Mold 1 and Graphite Outer Mold 2. Both are hollow structures, and they are snapped together to form a hollow graphite outer mold. The two outer molds are joined from left to right. Positioning steps 1 are machined at the same position on the upper end of the inner wall of both graphite outer molds. The dimensions of positioning steps 1 are adapted to the end of the core, allowing the end of the core substrate to engage with the positioning steps 1 during installation. After the end of the core substrate engages with the positioning steps 1, the gap between them is controlled within 0.2 mm.

[0043] S2. A hollow core matrix is ​​prepared using PLA plastic and 3D printing technology.

[0044] In this embodiment of the application, the prepared core substrate is a hollow structure with a thickness of 3mm. The shape of the core substrate is consistent with the complex internal cavity structure of the casting. A positioning groove 2 is provided on the upper outer wall of the core substrate. The overall size of the positioning groove 2 is smaller than the size of the positioning step 1, preferably less than 0.2mm.

[0045] S3. Apply a medium-temperature wax liquid with a temperature range of 80℃ to the inner cavity of the core substrate to form a medium-temperature wax layer. Then, clean the medium-temperature wax layer with wax remover and distilled water in sequence. Dry at 24℃ for 24 hours to obtain core substrate A.

[0046] In this embodiment, a medium-temperature wax liquid with a temperature range of 80°C is used to coat the inner cavity of the core substrate, thereby forming a medium-temperature wax layer in the inner cavity of the core substrate. Then, the medium-temperature wax layer is cleaned with a wax remover, and finally the residue is cleaned again with distilled water. The core substrate A is obtained by drying at 24°C for 24 hours.

[0047] S4. Apply two layers of surface slurry to the inner cavity of core substrate A, sprinkle surface sand after each layer, and dry at 21℃ for 24 hours to obtain core substrate B.

[0048] In this embodiment, two layers of surface slurry are applied to the inner cavity of the core substrate A. Surface sand is sprinkled after each layer of surface slurry is applied, resulting in a total surface coating thickness of 0.3 mm. The coating is dried at 21°C for 24 hours. Finally, the sand particles at the edge of the opening of the core substrate A are scraped off to obtain the core substrate B. The surface slurry is composed of a mixture of surface-specific adhesive and yttrium oxide powder, with a yttrium oxide powder:surface-specific adhesive ratio of 3.8-4.5:1. The surface sand is at least one of yttrium oxide or white corundum.

[0049] S5. Apply a layer of transition layer slurry to the inner cavity of core substrate B, sprinkle transition layer sand, and dry at 21℃ for 24 hours to obtain core substrate C.

[0050] In this embodiment, a transition layer slurry is applied to the inner cavity of the core substrate B, and transition layer sand (40-mesh mullite sand) is immediately sprinkled on top. The mixture is then dried at 21°C for 24 hours. The sand particles at the edges of the opening of the core substrate B are cleaned to obtain the core substrate C. The transition layer slurry consists of silica sol, wetting agent, bauxite powder, and mullite powder; the transition layer sand is fine mullite sand.

[0051] S6. Apply five layers of backing slurry to the inner cavity of the core substrate C. Sprinkle backing sand after each layer is applied. Dry at 25°C for 12 hours to obtain the core substrate D. After applying the third layer of backing sand, reinforce the inner cavity of the core substrate C with wire mesh and wrap and bind the outer wall of the core substrate C with wire.

[0052] In this embodiment, five layers of backing slurry are applied to the inner cavity of the core substrate C. After each layer of backing slurry is applied, backing sand (20-mesh mullite sand) is sprinkled on top. The mixture is dried at 25°C for 12 hours, and excess sand is removed from the edges of the opening of the core substrate C. After the third layer of backing sand is applied, a wire mesh of appropriate size is used to reinforce the inner cavity wall of the core substrate C. The outside of the substrate is wrapped and bound with φ1mm wire. After binding, backing slurry and backing sand are applied again. The backing slurry has the same composition as the transition layer slurry, and the backing sand is coarse mullite sand.

[0053] S7. At a temperature of 1050℃, the core substrate D is baked for 3 hours to burn off the core substrate A, and all the iron wires on the outer wall of the core substrate D are cut off to obtain the investment casting shell core.

[0054] In this embodiment, the core substrate D is baked at 1050°C for 3 hours to burn off the core substrate A. Then, all the iron wires on the outside of the core substrate D are cut off, thereby obtaining a casting shell core with a room temperature flexural strength of 11MPa, which is composed of multi-layer slurry, transition slurry, back slurry, and back sand. A docking groove corresponding to the positioning groove 2 is formed on the outside of the casting shell core.

[0055] S8. Install the investment casting shell core into the inner cavity of the graphite outer mold one, and make the mating groove engage with the positioning step 1 of the graphite outer mold one. Then, assemble and fix the graphite outer mold two with the graphite outer mold one to form a composite mold.

[0056] In this embodiment, the investment casting shell core is installed in the inner cavity of graphite outer mold one or graphite outer mold two, and the mating groove is engaged with the positioning step 1 of graphite outer mold one or graphite outer mold two. Then, the corresponding graphite outer mold one or graphite outer mold two are mated and positioned and connected by positioning pins to obtain a composite mold.

[0057] The casting process for the valve body of a small titanium or zirconium alloy gate valve is as follows: S1. Preheat the composite mold to 300℃ using a benchtop resistance furnace and hold for 1 hour to obtain a preliminary composite mold. This process is used to reduce the temperature difference between the composite mold and the molten metal, improve the fluidity of the molten metal, and facilitate filling.

[0058] S2. Under vacuum conditions, within a 10-second time period, titanium and zirconium alloy melt is steadily poured into the pores between the investment casting shell core and the graphite outer mold in the preliminary composite mold, and the temperature of the titanium and zirconium alloy melt is 80°C higher than the alloy liquidus temperature.

[0059] S3. After the titanium and zirconium alloy melt cools to room temperature, first remove the graphite outer mold, and then remove the investment casting shell and core by means of instruments or water blasting to obtain the titanium and zirconium alloy casting.

[0060] Example 3: This embodiment provides a method for preparing a composite mold and a casting process for titanium and zirconium alloy castings. Specifically, the composite mold is a composite mold for a small ball valve body, and the casting process for the titanium and zirconium alloy castings is the casting process for a small ball valve body.

[0061] The preparation method of the composite mold for a small ball valve body includes: S1. Graphite mold one and graphite mold two are prepared using high-purity, dense graphite electrode material. Graphite mold one and graphite mold two are connected and interlocked to form a hollow graphite mold.

[0062] In this embodiment, high-purity dense graphite electrode material with a bulk density of 1.78 g / cm³ and a room-temperature flexural strength of 43 MPa is selected. Two identical graphite outer molds, Element 1 and Element 2, are machined using a CNC machining center. Both are hollow structures, and they are snapped together to form a hollow graphite outer mold. Element 1 and Element 2 are joined from left to right. Positioning steps 1 are machined at the same position on the upper end of the inner wall of both Element 1 and Element 2. The dimensions of positioning steps 1 are adapted to the end of the core, allowing the end of the core substrate to engage with the positioning steps 1 during installation. The gap between the end of the core substrate and the positioning steps 1 is controlled within 0.2 mm after engagement.

[0063] S2. A hollow core matrix is ​​prepared using PLA plastic and 3D printing technology.

[0064] In this embodiment, the prepared core substrate is a hollow structure with a thickness of 5mm. The shape of the core substrate is consistent with the complex internal cavity structure of the casting. A positioning groove 2 is provided on the upper outer wall of the core substrate. The overall size of the positioning groove 2 is smaller than the size of the positioning step 1, preferably less than 0.2mm.

[0065] S3. Apply a medium-temperature wax liquid with a temperature range of 90℃ to the inner cavity of the core substrate to form a medium-temperature wax layer. Then, clean the medium-temperature wax layer with wax remover and distilled water in sequence. Dry at 26℃ for 24 hours to obtain core substrate A.

[0066] In this embodiment, a medium-temperature wax liquid with a temperature range of 90°C is used to coat the inner cavity of the core substrate, thereby forming a medium-temperature wax layer in the inner cavity of the core substrate. Then, the medium-temperature wax layer is cleaned with a wax remover, and finally the residue is cleaned again with distilled water. The core substrate A is obtained by drying at 26°C for 24 hours.

[0067] S4. Apply two layers of surface slurry to the inner cavity of core substrate A, sprinkle surface sand after each layer, and dry at 22℃ for 24 hours to obtain core substrate B.

[0068] In this embodiment, two layers of surface slurry are applied to the inner cavity of the core substrate A. Surface sand is sprinkled after each layer of surface slurry is applied, resulting in a total surface coating thickness of 0.5 mm. The coating is dried at 22°C for 24 hours. Finally, the sand particles at the edge of the opening of the core substrate A are scraped off to obtain the core substrate B. The surface slurry is composed of a mixture of surface-specific adhesive and yttrium oxide powder, with a yttrium oxide powder:surface-specific adhesive ratio of 3.8-4.5:1. The surface sand is at least one of yttrium oxide or white corundum.

[0069] S5. Apply a layer of transition layer slurry to the inner cavity of core substrate B, sprinkle transition layer sand, and dry at 22℃ for 24 hours to obtain core substrate C.

[0070] In this embodiment, a transition layer slurry is applied to the inner cavity of the core substrate B, and transition layer sand (40-mesh mullite sand) is immediately sprinkled on top. The mixture is then dried at 22°C for 24 hours. The sand particles at the edges of the opening of the core substrate B are cleaned to obtain the core substrate C. The transition layer slurry consists of silica sol, wetting agent, bauxite powder, and mullite powder; the transition layer sand is fine mullite sand.

[0071] S6. Apply seven layers of backing slurry to the inner cavity of the core substrate C, and sprinkle backing sand after each layer. Dry at 26°C for 12 hours to obtain the core substrate D. After applying the third layer of backing sand, attach wire mesh to the inner cavity of the core substrate C for reinforcement, and wrap and bind the outer wall of the core substrate C with wire.

[0072] In this embodiment, seven layers of backing slurry are applied to the inner cavity of the core substrate C. After each layer of backing slurry is applied, backing sand (20-mesh mullite sand) is sprinkled on top. The mixture is dried at 26°C for 12 hours, and excess sand is removed from the edges of the opening of the core substrate C. After the third layer of backing sand is applied, a wire mesh of appropriate size is used to reinforce the inner cavity wall of the core substrate C. The outside of the substrate is wrapped and bound with φ1mm wire. After binding, backing slurry and backing sand are applied again. The backing slurry has the same composition as the transition layer slurry, and the backing sand is coarse mullite sand.

[0073] S7. At a temperature of 1100℃, the core substrate D is baked for 2 hours to burn off the core substrate A, and all the iron wires on the outer wall of the core substrate D are cut off to obtain the investment casting shell core.

[0074] In this embodiment, the core substrate D is baked at 1100°C for 2 hours to burn off the core substrate A. Then, all the iron wires on the outside of the core substrate D are cut off, thereby obtaining a casting shell core with a room temperature flexural strength of 11MPa, which is composed of multi-layer slurry, transition slurry, back slurry, and back sand. A docking groove corresponding to the positioning groove 2 is formed on the outside of the casting shell core.

[0075] S8. Install the investment casting shell core into the inner cavity of the graphite outer mold one, and make the mating groove engage with the positioning step 1 of the graphite outer mold one. Then, assemble and fix the graphite outer mold two with the graphite outer mold one to form a composite mold.

[0076] In this embodiment, the investment casting shell core is installed in the inner cavity of graphite outer mold one or graphite outer mold two, and the mating groove is engaged with the positioning step 1 of graphite outer mold one or graphite outer mold two. Then, the corresponding graphite outer mold one or graphite outer mold two are mated and positioned and connected by positioning pins to obtain a composite mold.

[0077] A casting process for titanium-zirconium alloy castings, the specific steps of which are as follows: S1. Preheat the composite mold to 350℃ using a benchtop resistance furnace and hold for 1.5 hours to obtain a preliminary composite mold. This process is used to reduce the temperature difference between the composite mold and the molten metal, improve the fluidity of the molten metal, and facilitate filling.

[0078] S2. Under vacuum conditions, within a 15-second time period, titanium and zirconium alloy melt is steadily poured into the pores between the investment casting shell core and the graphite outer mold in the preliminary composite mold, and the temperature of the titanium and zirconium alloy melt is 120°C higher than the alloy liquidus temperature.

[0079] S3. After the titanium and zirconium alloy melt cools to room temperature, first remove the graphite outer mold, and then remove the investment casting shell and core by means of instruments or water blasting to obtain the titanium and zirconium alloy casting.

[0080] It should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Those skilled in the art can modify the technical solutions described in the above embodiments, or make equivalent substitutions for some of the technical features; and all such modifications and substitutions should fall within the protection scope of the appended claims of the present invention.

Claims

1. A method for preparing a composite mold, characterized in that, The method includes: Graphite outer mold one and graphite outer mold two are prepared using graphite electrode material. Graphite outer mold one and graphite outer mold two have the same structure and are connected and snapped together to form a hollow graphite outer mold. A hollow core matrix was prepared using PLA plastic and 3D printing technology. Apply a medium-temperature wax liquid with a temperature range of 70-90℃ to the inner cavity of the core substrate to form a medium-temperature wax layer. Then, clean the medium-temperature wax layer with wax remover and distilled water in sequence. Dry it at a temperature of 22℃-26℃ for 24 hours to obtain core substrate A. Two layers of surface slurry were applied to the inner cavity of core substrate A, and surface sand was sprinkled after each layer was applied. The core substrate B was obtained by drying at 20℃-22℃ for 24 hours. Apply a layer of transition layer slurry to the inner cavity of core substrate B, sprinkle transition layer sand on it, and dry it at 20℃-22℃ for 24 hours to obtain core substrate C; Five to ten layers of backing slurry are applied to the inner cavity of the core substrate C. Backing sand is sprinkled on each layer. The core substrate D is obtained by drying at 24℃-26℃ for 12 hours. At a temperature of 1050℃-1150℃, the core matrix D is calcined for 2-4 hours, and the core matrix A is burned off to obtain the investment casting shell core. The investment casting shell core is installed in the graphite outer mold one, and then the graphite outer mold two is connected and fixed to the graphite outer mold one to form a composite mold.

2. The method for preparing a composite mold according to claim 1, characterized in that, The graphite electrode has a bulk density of 1.75 g / cm³-1.80 g / cm³ and a flexural strength at room temperature of 40 MPa-45 MPa.

3. The method for preparing a composite mold according to claim 1, characterized in that, The upper end of the inner cavity of the graphite outer mold 1 and the graphite outer mold 2 is provided with a positioning step (1) at the same position, and the upper end of the core substrate is provided with a positioning groove (2) that fits the positioning step (1).

4. The method for preparing a composite mold according to claim 1, characterized in that, Apply five to ten layers of backing slurry to the inner cavity of the core substrate C. Sprinkle backing sand after each layer is applied. After the third layer of backing sand is applied, attach wire mesh to the inner cavity of the core substrate C and wrap and bind it with wire on the outer wall of the core substrate C.

5. The method for preparing a composite mold according to claim 4, characterized in that, The core substrate D is baked at 1050℃-1150℃ for 2-4 hours. After the core substrate A is burned off, all the iron wires on the outer wall of the core substrate D are cut off.

6. A composite mold, characterized in that: The composite mold is prepared based on the composite mold preparation method described in any one of claims 1-5.

7. A casting process for titanium and zirconium alloy castings, said casting process being implemented based on the composite mold described in claim 6, characterized in that, The casting process includes: The composite mold is preheated to 300℃-400℃ using a tabletop resistance furnace and held at that temperature for 1-2 hours to obtain a preliminary composite mold. In a vacuum environment, within a time period of 6s-15s, titanium and zirconium alloy melt is steadily poured into the pores between the investment casting shell core and the graphite outer mold in the preliminary composite mold. After the titanium and zirconium alloy melt cools to room temperature, the graphite outer mold is removed first, and the investment casting shell and core are removed by means of instruments or water blasting to obtain the titanium and zirconium alloy casting.

8. The casting process for a titanium-zirconium alloy casting according to claim 7, characterized in that: The temperature of the titanium and zirconium alloy melt is 80℃-120℃ higher than the alloy liquidus temperature.